New methods of ecologicaly safe recycling of invalid foamagent - Shatunov С.Б.; Stashevsky Е.В. (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
Currently existing methods of utilization of substandard foaming agent are considered, disadvantages of each of them are indicated. The necessity of creation of a new method allowing to utilize the lost properties of foaming agent with minimum costs and damage to the environment is shown. A fundamentally new method of environmentally safe costless utilization of substandard foaming agent is proposed.